Integrasi Soft Skills, Hard Skills dan Entrepreneur Skills melalui Pembelajaran Teaching Factory - Susanto, Arif; Rahmawati, Fitri; Prasetya, Prima Adi (STKIP PGRI Bandar Lampung, 2024)
Learning in Vocational High Schools (SMK) needs to be developed to prepare its graduates to meet the needs of complete competencies expected by the world of work or industry. The purpose of this study was to determine the increase in work competencies with the integration of soft skills, hard skills, and entrepreneur skills in SMK students through the application of the teaching factory learning model. The method used was a quasi-experimental, descriptive quantitative approach. The population in this study were grade XII students of the Automotive Engineering Expertise Program at SMK YPT Purworejo and sample collection using a purposive sampling technique. Data were collected using cognitive tests, questionnaires, observations, interviews and documentation studies. The data obtained were then analyzed descriptively and presented in the form of a descriptive report. The results of the study showed that there was an increase and development of soft skills, hard skills, entrepreneur skills and cognitive abilities of grade XII students of the Automotive Engineering Expertise Program at SMK YPT Purworejo at very high or positive significant criteria.